2021
DOI: 10.1016/j.cej.2021.130637
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally stable Pd/SiO2@Zr Core@Shell catalysts for diesel oxidation applications

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The microreactor experiments were performed in a custom‐built reactor system, as reported previously 33,34 . The experimental procedure followed is shown in Scheme 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microreactor experiments were performed in a custom‐built reactor system, as reported previously 33,34 . The experimental procedure followed is shown in Scheme 1.…”
Section: Methodsmentioning
confidence: 99%
“…The microreactor experiments were performed in a custom-built reactor system, as reported previously. 33,34 The experimental procedure followed is shown in Scheme 1. Specifically, 100 mg of sample (HBEA, Pd/BEA, 250-500 μm) was loaded in a U-shaped quartz reactor (I.D.…”
Section: Microreactor Experimentsmentioning
confidence: 99%
“…Kinetic studies were conducted in a packed-bed reactor as reported previously. , Specifically, 100 mg of Ni/CeO 2 catalyst was diluted with 100 mg of inert quartz sand and loaded in a U-shaped quartz reactor (ID = 8 mm). The feed gas contained a mixture of CH 4 , O 2 , and Ar with a flow rate of 30 sccm (cm 3 /min at STP) and a gas hourly space velocity (GHSV) of ∼18 000 mL g –1 h –1 .…”
Section: Methodsmentioning
confidence: 99%
“…The CH 4 oxidation performance of the as-synthesized catalysts was evaluated in a home-built packed bed reactor equipped with an online MKS FTIR gas analyzer (MultiGas 2030). , The catalyst (100 mg, 250–500 μm) was loaded into a U-shaped quartz tube reactor (I.D. = 8 mm) and was stabilized between two small plugs of quartz wool.…”
Section: Experimental Sectionmentioning
confidence: 99%